Approach of Da’wah - Kaddas, Badruddin; Ishak, Ismail (Tun Dr. Mahathir Mohamad Thoughts Institute (IPDM), 2018)
In the era of development of information and communication technology today, The da'i are required to prepare themselves to participate in the escort. A da'i should be adept at exploiting a wide range of mass media. The Radio is one of the mass media is still very popular to be da'wah media because it has characteristics that are typical compared with other media. The existence of today's media leads to the transmission of information from one source to another source. This study discusses the concept of use radio media as the da'wah media.